2018
DOI: 10.1161/atvbaha.118.310990
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide Reduces Postprandial Hyperlipidemia by Increasing ApoB48 (Apolipoprotein B48) Catabolism and by Reducing ApoB48 Production in Patients With Type 2 Diabetes Mellitus

Abstract: Objective-Treatment with liraglutide, a GLP-1 (glucagon-like peptide-1) agonist, has been shown to reduce postprandial lipidemia, an important feature of diabetic dyslipidemia. However, the underlying mechanisms for this effect remain unknown. This prompted us to study the effect of liraglutide on the metabolism of ApoB48 (apolipoprotein B48). Approach and Results-We performed an in vivo kinetic study with stable isotopes (D 8 -valine) in the fed state in 10 patients with type 2 diabetes mellitus before treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
66
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 46 publications
(54 reference statements)
4
66
2
1
Order By: Relevance
“…This was confirmed in humans by Vergès and colleagues, who recently reported on the effects of liraglutide on the metabolism of ApoB‐48 . Treatment with liraglutide significantly decreased postprandial hyperlipidaemia in subjects with T2D via a mechanism of reduced ApoB‐48 production and increased ApoB‐48 catabolism …”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations
“…This was confirmed in humans by Vergès and colleagues, who recently reported on the effects of liraglutide on the metabolism of ApoB‐48 . Treatment with liraglutide significantly decreased postprandial hyperlipidaemia in subjects with T2D via a mechanism of reduced ApoB‐48 production and increased ApoB‐48 catabolism …”
Section: Discussionmentioning
confidence: 52%
“…In a series of studies in hamsters and mice, Hsieh and colleagues showed that the GLP‐1 receptor is essential for regulation of the intestinal lipid and lipoprotein metabolism, through control of intestinal lipoprotein synthesis and secretion . This was confirmed in humans by Vergès and colleagues, who recently reported on the effects of liraglutide on the metabolism of ApoB‐48 . Treatment with liraglutide significantly decreased postprandial hyperlipidaemia in subjects with T2D via a mechanism of reduced ApoB‐48 production and increased ApoB‐48 catabolism …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…It follows that development of a true picture of the physiology of TRLs requires investigation of the non-steadystate dynamics of chylomicron metabolism overlayered on the (near) steady-state system of VLDL kinetics. To date, this has been difficult to achieve and it has been necessary to use analytical approaches that are arguably over-simplistic and/or employ nonphysiological nutritional regimens [8][9][10][11]. For example, previous studies of apoB48 metabolism have utilized a continuous micro-meal feeding pattern to generate a quasisteady state or used a single metabolic compartment to represent chylomicron kinetics following a test meal [8,9,[12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%